2020
DOI: 10.1039/d0ob01550d
|View full text |Cite
|
Sign up to set email alerts
|

Stereocontrolled transformations of cyclohexadienone derivatives to access stereochemically rich and natural product-inspired architectures

Abstract: The last two decades or so have witnessed an upsurge in defining the art of designing complex natural products and nature-inspired molecules. Throughout these decades fundamental insights into stereocontrolled, step-economic...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(15 citation statements)
references
References 128 publications
0
15
0
Order By: Relevance
“…(2aR,6aR,14bS)-2a-Methoxy-2,2a,3,4,6,6a,8,9,14,14bdecahydroindolo[2′,3′:3,4]pyrido[1,2-a]quinolin-5(1H)-one (4a). White solid, 58 mg, 90% yield; mp 183−185 °C; R f = 0.45 (silica gel, 1:1 hexane/EtOAc); 1 [3,4-b]indol-5(2aH)-one (7). Off-white solid, 57.0 mg, 92% yield; mp 236−238 °C; R f = 0.5 (silica gel, 1:1 hexane/EtOAc); 1 H NMR (500 MHz, CDCl 3 ) δ 7.74 (s, 1H), 7.49 (d, J = 7.7 Hz, 1H), 7.32 (d, J = 7.9 Hz, 1H), 7.16 (t, J = 7.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
See 1 more Smart Citation
“…(2aR,6aR,14bS)-2a-Methoxy-2,2a,3,4,6,6a,8,9,14,14bdecahydroindolo[2′,3′:3,4]pyrido[1,2-a]quinolin-5(1H)-one (4a). White solid, 58 mg, 90% yield; mp 183−185 °C; R f = 0.45 (silica gel, 1:1 hexane/EtOAc); 1 [3,4-b]indol-5(2aH)-one (7). Off-white solid, 57.0 mg, 92% yield; mp 236−238 °C; R f = 0.5 (silica gel, 1:1 hexane/EtOAc); 1 H NMR (500 MHz, CDCl 3 ) δ 7.74 (s, 1H), 7.49 (d, J = 7.7 Hz, 1H), 7.32 (d, J = 7.9 Hz, 1H), 7.16 (t, J = 7.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…Several studies have reported on the use of nature-inspired compounds for developing next-generation high-sp 3 content therapeutics that effectively treat unmet medical needs. This concept is further supported by the fact that natural products represent a rich source of structural diversity. However, several challenges continue to limit their utility in biological screening campaigns, relative to their limited quantities available for detailed structure–activity relationship studies. Hence, complexity-to-diversity (CtD) strategies for the de novo design of nature-inspired compounds required for phenotypic screening programs have been employed by many groups. , Thus, the development of new CtD strategies for rapid access to complex compound collections exhibiting sufficient stereochemical and skeletal diversity remains a challenge.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, numerous transition metal catalysis and organocatalysis have been utilized for the asymmetric desymmetrization of cyclohexadienones. [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] Recently, aza-Michael/Michael cyclization, a potentially powerful reaction to construct aza-cyclic complex molecules, was designed for the asymmetric desymmetrization of aza-cyclohexadienones.…”
Section: Introductionmentioning
confidence: 99%
“…Most of these functionalizations have been studied with protected pyrroles. ,, Furthermore, use of expensive metals, limited substrate scope, and regioselectivity are the major issues of concern (Scheme a). On the other hand, cyclohexa-2,5-dienones are potent prochiral building blocks and have been greatly used for the construction of bicyclic and polycyclic architectures . Along this line, most of the progress was achieved with alkynyl tethered dienone 1 in the presence of external or internal nucleophiles (Scheme b). , We have also used this line for the synthesis of hydronaphtho­[1,8- bc ]­furans and tetracyclic aminals .…”
mentioning
confidence: 99%
“…On the other hand, cyclohexa-2,5-dienones are potent prochiral building blocks and have been greatly used for the construction of bicyclic and polycyclic architectures . Along this line, most of the progress was achieved with alkynyl tethered dienone 1 in the presence of external or internal nucleophiles (Scheme b). , We have also used this line for the synthesis of hydronaphtho­[1,8- bc ]­furans and tetracyclic aminals . Furthermore, cyclohexa-2,6-dienones or p -quinols are known to be an “aromatic to be” electrophilic surrogate to afford functionalized arenes and biaryls .…”
mentioning
confidence: 99%